The Role of the Supply Chain Management in Responsibility of Indonesian Government Auditors in Detecting Corruptions: Analysis of Cognitive and Moral Effects - Yusnaini Yusnaini; Burhanuddin Burhanuddin; Arista Hakiki (International Journal of Supply Chain Management, 2020)
Abstract- This study tends to examining how a new analytical tool, can be useful to detect the fraudulent activities in Supply Chain Management. This study aims to analyze and provide empirical evidence regarding the perception of the Indonesian government's internal auditors' responsibility in detecting corruption. The theory of triangle model of responsibility [29] is used as a reference for analyzing research results. The 2x2 between experimental subjects design was conducted to investigate the research questions. The cognitive style tested is field style independent and field dependent, while the moral of the auditor is divided into high and low levels. The Participants are 92 internal government auditors in Indonesia. Results show that perceptions of responsibility for detecting corruption among groups that are field independent and dependent fields differ significantly. Thus the perception of responsibility for detecting corruption is higher for auditors with independent field cognitive style (FI) than for auditors with field dependent (FD) cognitive styles. Furthermore, the results show that the perception of responsibility for detecting corruption is higher for auditors with a high level of moral development than a low moral development level.